PERANCANGAN SISTEM PEMANTAU RUANGAN UNTUK KEAMANAN BARANG BERHARGA SECARA WIRELESS - Haryadi, Hartono; Winata, Tony; Hartanto, Hartanto (Universitas Tarumanagara, 2006)
In an exhibition needs high-quality security to prevent burglary, such as in museum that many have historical things. Security system that have been made used infrared for the sensor, if this sensor is disturbed then the DC motor will move down and also sending the data which cabinet is troubled.